L’oeuvre romanesque de Loys Masson, ou l’écocritique mauricienne et indianocéanique au moyen d’une poétisation de la nature et de l’espace - Samboo, Sachita R. (Romanica Silesiana, 2020)
The study of Mauritian Literature and the environment from an interdisciplinary perspective arouses various concerns and questionings such as the protection of planet Earth, the relation between characterisation and natural settings, the nature-culture dichotomy and nature writing. The fictionalisation and poeticization of Mauritian and Indian Ocean islands’ natural spaces in Loys Masson’s novels depict both man as Nature’s saviour and Nature as man’s saviour, in such a way that Nature’s raison d’être becomes Literature and aesthetics. Nature exists because it will eventually turn into a Book. Born at the end of the 20th century in American universities and closely linked to geocriticism and ecopoetics, ecocriticism thus provides new insights into Masson’s novels while reviving traditional French philosophical thoughts by Jean-Jacques Rousseau or Michel Serres.